27.27 Product Class 27: 1,2-Diimines - Isovitsch,R. (Knowledge Updates 2021/2, 2021)
The utility of 1,2-diimines (α-diimines, 1,4-diazabutadienes) stems from the ease with which their steric and electronic properties can be tailored to a specific use. Current interest in this area involves using 1,2-diimines as precursors for novel bioactive compounds, as well as transition-metal ligands for the formation of novel polymerization catalysts and chemotherapeutic agents. In this review, the fundamental approaches for the synthesis of 1,2-diimines are described, as well as a current sampling of the unique ways that they are used to solve research problems. The chapter is organized based on the ways that 1,2-diimines are synthesized: condensation reactions and metal-promoted methods.
Keywords: Referencework; Science of Synthesis; diimines; azomethines; Schiff bases; diketones; anilines; condensation reactions